Extraction of Bioactive Proteins from Seeds (Corn, Sorghum, and Sunflower) and Sunflower Byproduct: Enzymatic Hydrolysis and Antioxidant Properties - Prado, Danielle M. F. do; Almeida, Adrielle B. de; Oliveira Filho, Josemar G. de [UNESP]; Alves, Cassia C. F.; Egea, Mariana B.; Lemes, Ailton C. (Bentham Science Publ Ltd, 2021)
Background: Food proteins have benefits for human health, which justifies their production and use. In this context, the use of seeds and byproducts that would be otherwise discarded is highlighted in the present work, to produce protein extracts and hydrolyzed proteins, generating opportunities to reduce environmental impacts. Objective: This work aimed to use different extraction methods to obtain protein extracts from seeds (corn, sorghum, and sunflower) and sunflower byproduct to determine their antioxidant activity, and apply different proteolytic enzymes in the hydrolysis of sunflower byproduct. Methods: The seeds of corn, sorghum, and sunflower, and sunflower byproduct were ground to produce flour and the protein extracts were prepared using five different methods. The bioactivity of fractions was analyzed by different methods (ABTS, DPPH, and FRAP) to evaluate the antioxidant activity. Results: The most effective methods, which resulted in higher protein extraction and antioxidant activity, were those in which NH4HCO3 (5 mM, pH 8.0) and H2O/C2H6O (2:3) were used. The highest protein contents were 797.9, 303.8, and 11296.5 mu g/g, and the highest antioxidant activity was 34417.5, 9732.6, and 47473.1 mu g TE/g from Soxhlet and Bligh and Dyer defatted extractions for sunflower seed, and sunflower byproduct, respectively. Regarding enzymatic hydrolysis, sunflower byproduct was the substrate that presented the highest degree of hydrolysis (11.06%) when Neutrase (R) enzyme was used. Enzymatic hydrolysis increased antioxidant activity in the hydrolyzed proteins, approximately by 20.0%, using Neutrase (R) Neutrase and 22.3% using Flavourzyme (R) Flavourzyme treatments. Conclusion: The protein extracts and the hydrolyzed proteins exhibited high antioxidant activity, demonstrating great potential for use as natural antioxidants in food systems.
Keywords: Extraction methods; protein extraction; hydrolysis; proteolytic enzymes; byproducts; natural antioxidants